Contemporary social work practice - Dewees, Marty (McGraw-Hill, 2006)
The second of five books in McGraw-Hill's new series NEW DIRECTIONS IN SOCIAL WORK, this text helps translate the guiding theoretical perspectives of social justice, human rights, and critical social construction into purposeful social work practice. Each new copy of the text is packaged free with a companion interactive CD-ROM offering case studies based on actual practice situations, as well as a concise ethics primer!